Abnormal Placental Cord Insertion and Adverse Pregnancy Outcomes: Results from a Prospective Cohort Study - Ismail, Khadijah I.; Hannigan, Ailish; Kelehan, Peter; O'Donoghue, Keelin; Cotter, Amanda (American Journal of Perinatology, 2017)
Objectives To prospectively measure the distance from the placental cord insertion (PCI) site to the placental margin using digital imaging and to examine the association between abnormal PCI and adverse pregnancy outcomes in singleton pregnancies.Study Design This prospective cohort study examined 1,005 placentas from consecutively delivered singleton pregnancies in a tertiary center. Standardized images of each placenta were taken and digital measurement was performed using ImageJ software.Results The rates of velamentous (insertion into the membrane) and marginal (<2 cm from placental margin) cord insertions in a total of 1,005 singleton pregnancies were 3.6% (n  =  36; 95% confidence interval [CI]  =  2.5–4.9%) and 6.4% (n  =  64; 95% CI  =  4.9–8.1%), respectively. Abnormal PCI was found to be more common among smokers compared with non-smokers (22.7 vs. 14.8%, p = 0.04). Abnormal PCI was found to be significantly associated with small for gestational age (adjusted odds ratio [OR]: 1.73; 95% CI: 1.01–2.97, p = 0.047) and low birth weight (adjusted OR: 3.87; 95% CI: 1.72–8.71, p = 0.001).Conclusion Digital imaging analysis using ImageJ software mapped the surface of the placenta and provided objective measurement of PCI site. In this large prospective cohort, abnormal PCIs were significantly associated with an increased risk of small for gestational age and low birth weight.
Keywords: abnormal cord insertion; digital measurements; low birth weight; marginal cord insertion; objective measurements; placental cord insertion; singletons; small for gestational age; velamentous cord insertion